2010
DOI: 10.1016/j.optcom.2010.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Practical method to estimate the standard deviation in absorption coefficients measured with THz time-domain spectroscopy

Abstract: a b s t r a c tA model of standard deviation in the intensity spectrum of electric field observed with the terahertz timedomain spectroscopy (THz-TDS) is proposed to estimate the random error in the transmittance and absorption coefficients from a single or a few measurements of a sample. The proposed standard deviation which is derived on the basis of the statistical standard deviation and noise floor of intensity spectrum of reference fits well to the standard deviation of transmittance as well as absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 12 publications
(13 reference statements)
2
7
0
Order By: Relevance
“…Figure 1 shows a mean intensity of spectrum and the standard deviation of sixteen reference data without a sample in transmission measurements obtained using our THz-TDS system. Recently, it has been found that the standard deviation is almost proportional to the signal intensity and approaches to the noise floor at the lowest intensity signal region [5] and such a feature is similarly seen in Fig. 1.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…Figure 1 shows a mean intensity of spectrum and the standard deviation of sixteen reference data without a sample in transmission measurements obtained using our THz-TDS system. Recently, it has been found that the standard deviation is almost proportional to the signal intensity and approaches to the noise floor at the lowest intensity signal region [5] and such a feature is similarly seen in Fig. 1.…”
Section: Introductionsupporting
confidence: 61%
“…An interesting thing about the SNR is that the almost same maximum values have been obtained with different THz-TDS systems as shown in Ref. [5]. Therefore, a mechanism of occurrence of the random error may be identical between those systems.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Based on the empirical observation that the standard deviation (SD) of the THz spectral amplitude is proportional to the amplitude itself ( see Fig. 2a), Tripathi et al [8] derive a simple and very useful method for estimating the standard deviation of absorption coefficients. The SD of measured amplitude is assumed to be approximately given by α max is larger for the thinner sample.…”
Section: B Consequences Of Frequency-dependent Dynamic Range and Ampmentioning
confidence: 99%
“…Delay lines, for instance, have mechanical specifications with an accuracy between 0.1 and 1 m. However, the largest influence is due to thermal drifts, 14 which requires frequent reference scans to minimize the accumulated error. 15 The reference zero delay of our system drifts by approximately 20 fs/h. This is reasonable, as the free-space optics is mounted on a stainless-steel table ͑thermal expansion coefficient 17.3 m / m°C͒.…”
mentioning
confidence: 97%